Processo de estabelecimento de um serviço de alta complexidade na saúde auditiva (2004-2009): caracterização, audiológica, demográfica e organizacional - Silva, Tatiane Alencar (2011)
Introduction: Hearing impairment is considered a public health problem by the impact of sensory deprivation on child development as well as it´s prevalence. Hearing Health Policy in Brazil was boosted after the Ministry of Health published the National Ordinance Hearing Health Care in 2004. After the six years of implementation, it is time to evaluate actions and propose improvements. Goal: The aim of this study is to describe and analyze demographic, audiological and organizational processes of the Center for Hearing in Children (Centro de Audição na Criança - CeAC), a service that provides of high complexity procedures within the municipal network of the Secretary of Health of Sao Paulo, aimed at children from birth to age three, within the period 2004 to 2009. Method: During the study period, 3000 patients were registered in the service database. Of these, we selected 865 records of patients who completed the diagnostic process. The data from the charts were analyzed using descriptive and inferential analysis of demographic and audiological characteristics of the population, and some aspects of the intervention with hearing aids, analyzing trends over the period studied within annual intervals.Results: The results show that 54% of children diagnosed with hearing loss are male. As for region of residence, 75.8% lived in São Paulo, of whom 47.9% were residents of regions of references CeAC. The percentages of subjects with hearing loss are not all alike in the years 2004 to 2009. Regarding the degree and type of hearing loss, there is predominance profound hearing loss; when considering patients with unilateral hearing, loss there was predominantly conductive hearing loss. Among those with bilateral hearing loss, there was predominantly neurosensory hearing loss. The average age of diagnosis of children referred by Hospitals is smaller than in other categories. The chance of hearing impairment in Espontaneous Demand is higher than in hospital. There are significant differences between the distributions of age at diagnosis, degree and type of hearing loss. Method: During the study period, 3000 patients were registered in the service database. Of these, we selected 865 records of patients who completed the diagnostic process. The data from the charts were analyzed using descriptive and inferential analysis of demographic and audiological characteristics of the population, and some aspects of the intervention with hearing aids, analyzing trends over the period studied within annual intervals.Results: The results show that 54% of children diagnosed with hearing loss are male. As for region of residence, 75.8% lived in São Paulo, of whom 47.9% were residents of regions of references CeAC. The percentages of subjects with hearing loss are not all alike in the years 2004 to 2009. Regarding the degree and type of hearing loss, there is predominance profound hearing loss; when considering patients with unilateral hearing, loss there was predominantly conductive hearing loss. Among those with bilateral hearing loss, there was predominantly neurosensory hearing loss. The average age of diagnosis of children referred by Hospitals is smaller than in other categories. The chance of hearing impairment in Espontaneous Demand is higher than in hospital. There are significant differences between the distributions of age at diagnosis, degree and type of hearing loss